“Court from Away but Marry Close to Home”: Women, Marriage and Interpersonal Relations in Placentia Bay, Newfoundland - Powers, Ann Marie; Tye, Diane (Ethnologies, 2011)
Belonging is important in Newfoundland and Labrador but with its long history of patrilocality, where and to whom have women belonged? Here we consider how women who married into new families and communities in the Placentia Bay area of the province over a fifty year period (1943-1993) negotiated a place for themselves. The women, sometimes in complicity with their mothers-in-law, managed to create physical and social space through a variety of informal strategies, from managing gossip to creating a separate living space in their in-laws’ home. Some wives eventually developed a sense of belonging while others were never able to shake off their status as strangers and always felt like outsiders.